SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN SANKSI KETERLAMBATAN PERIZINAN SANTRI DENGAN MENGGUNAKAN METODE AHP - Muhammad Misdram (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Yudharta Pasuruan)
Decision Support System For Determining Sanctions DelayLicensing Pupils Method Using AHPThis study uses the title Decision Support System For Determining Sanctions DelayLicensing Pupils Method Using AHP. Sanctions are sanctions are moderate and mild categories. Determining sanctions on students to easily and according to UHPN. Ahp method is a method of splitting a complex or complicated problems in the unstructured situation into its component parts. incorporates considerations and personal judgment in a logical way and influenced the imagination, experience, and knowledge to develop a hierarchy of problems based on logic, intuition and experience to give consideration. AHP is a process to identify, understand and provide an estimate of the overall system interaction. AHP calculation results are not different from the results of the calculations are done manually, it is intended by the outcome CR <0.1, then the ratio of the consistency of the calculation can be accepted. If sebliknya repeated using even numbers.